Fifty shades darker - James, E. L. (James, E. L. Fifty shades trilogy v2, 2011)
Daunted by the singular sexual tastes and dark secrets of the beautiful, tormented young entrepreneur Christian Grey, Anastasia Steele has broken off their relationship to start a new career with a Seattle publishing house.